Implementation Of Monitoring and Control Temperature and Humidity Based on IoT in The Oyster Mushroom Cultivation Room - Wibowo, Budi Cahyo; Rozaq, Imam Abdul; Pratama, Tredi Pratama (Program Studi Teknik Elektro Universitas Khairun, 2023)
Oyster mushroom is one of the favorite horticultural commodities consumed by Indonesian people. In the cultivation of oyster mushrooms, there are many obstacles faced by farmers, including the difficulty in maintaining the temperature and humidity of the kumbung room so that to maintain the stability of temperature and humidity, farmers must always check and do regular watering. With these problems, a temperature and humidity monitoring and control system is needed to maintain the stability of temperature and humidity in oyster mushroom cultivation by automatically watering and heating the room temperature of the kumbung. The design of the system was designed based on the results of interviews with oyster mushroom farmers regarding the constraints faced, then proceed with the design and manufacture of hardware and software for an IoT-based oyster mushroom kumbung watering and heating system. The result of this research is that the system can respond to changes in temperature and humidity conditions in the kumbung room by automatically watering and heating the kumbung room. To return to the setpoint temperature value (25oC-28oC), it is necessary to heat the kumbung room with an average duration of heating of 383 seconds, and to return to the setpoint humidity value (75%-90%), it is necessary to water the kumbung room with an average watering time of 115 seconds.